Empowering humans in a cyber-physical production system: human-in-the-loop perspective - Costa, David (2020)
In the Industry 4.0 context, humans are taking upnew roles in Cyber-Physical Systems (CPS) since it was realizedthat they constitute the most flexible part of an automated system.With this new reality, humans are becoming integral parts ofCPS, entering in the realm of the Human-in-the-Loop of Cyber-Physical Systems (HiLCPS). In this paper, the challenges andtechnologies for the integration of humans in CPS environmentsare briefly discussed, and a practical application of the HiLCPSconcept is presented. For this purpose, a human operation workbench is empowered with intelligent decision and assistant systems that use, among others, reasoning algorithms, image processing and speech recognition, to improve the productivityand quality of the tasks performed by humans, particularly focusing the assembly of highly customized products, as well as the training of operators to perform complex assembly, repairing or maintenance tasks.